Going Online Together: The Potential for Mental Health Workers to Integrate Recovery Oriented E-Mental Health Resources Into Their Practice. Issue 2 (1st May 2018) - Williams, Anne; Fossey, Ellie; Farhall, John; Foley, Fiona; Thomas, Neil
Abstract : Background : The Internet offers a growing range of e-mental health resources for people experiencing severe mental illness. How these resources may be used in face-to-face interactions with consumers in mental health practice is not well understood. Aim : This article explores mental health workers' current use of online resources and their views about integrating e-mental health resources for promoting self-management and recovery into community-based practice. Method : A total of 37 mental health workers from six services attended focus groups to discuss their views about using online and e-mental health resources in face-to-face interactions with consumers. Data were analyzed using qualitative content analysis. Results : Participants described accessing Internet information but having little opportunity to use online resources with consumers. Limited access to mobile technology and perceptions that consumers lacked technological experience constrained current use. Three approaches to using e-mental health resources were perceived: directing, collaborating, and empowering. Access to mobile technology within worker–consumer interactions was identified as a potential catalyst for creating recovery-oriented therapeutic relationships. Conclusion : Mental health workers are ready to grasp opportunities to use e-mental health resources with consumers. This has the potential to develop and strengthen collaborative, partnership-based relationships if mental health services support workers and consumers to use online resources together.